PERHITUNGAN HARGA POKOK PRODUKSI DALAM MENENTUKAN HARGA JUAL PRODUK PADA MITRA IKAPRI - Henik Hari Astuti; Ayu Aulia Oktaviani; Ariani, Marieta; Desrawani Situmeang; Hisyam Ramadhan (Universitas Trisakti, 2025)
This training activity aims to enhance the understanding of members of the Ikatan Kartini Profesional Indonesia (IKAPRI) regarding the concept and methods of calculating Production Cost (Harga Pokok Produksi/HPP), as well as to equip entrepreneurs with practical skills to accurately calculate HPP in determining competitive and profitable product selling prices. In today’s competitive business environment, a deep understanding of HPP is a crucial foundation for MSMEs in financial management and optimal pricing strategy development. This training was designed to address the challenges faced by MSME entrepreneurs in accurately calculating production costs, which often become a significant barrier to business growth. The activity was conducted using interactive training and counseling methods, in which participants were actively engaged in discussions and practical HPP calculation exercises. The IKAPRI MSME participants demonstrated high enthusiasm, evident from their active involvement in every discussion and question-and-answer session. As part of the evaluation, questionnaires were distributed to measure participants’ comprehension of HPP concepts and calculations. The evaluation results indicated that 54.55% of the participants achieved a very good level of understanding, while another 36% demonstrated a fairly good understanding. Through this training, it is expected to encourage more professional and efficient business management among MSME practitioners, particularly those within IKAPRI. Enhancing capacity in production cost management will ultimately contribute to business sustainability through better business decision-making and increased market competitiveness.